1995
DOI: 10.5980/jpnjurol1989.86.1538
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of 7 Renal Cell Carcinoma Patients Developing a Solitary Pancreatic Metastasis After Nephrectomy

Abstract: In conclusion, renal cell carcinoma accompanied by later development of pancreatic metastasis tend to occur in younger patients and have higher incidence in females than in males when compared with otherwise similar renal cell carcinomas. Furthermore, they tend to be of low stage and grade, have longer intervals to the occurrence of metastasis and carry a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…Renal cell carcinoma is more notorious for being problematic in this regard. In a review of 752 renal cell carcinomas over a span of 38 years, it was found that 0.9% developed solitary pancreatic metastasis [65]. In many instances, the interval after the diagnosis to the development of metastasis was several years, sometimes even decades [1,3,4,15,18,21,23,26,28,30,31,34,65,66,71,74,83,86,87,89,93,94,98].…”
Section: Discussionmentioning
confidence: 99%
“…Renal cell carcinoma is more notorious for being problematic in this regard. In a review of 752 renal cell carcinomas over a span of 38 years, it was found that 0.9% developed solitary pancreatic metastasis [65]. In many instances, the interval after the diagnosis to the development of metastasis was several years, sometimes even decades [1,3,4,15,18,21,23,26,28,30,31,34,65,66,71,74,83,86,87,89,93,94,98].…”
Section: Discussionmentioning
confidence: 99%
“…Our experience was supported by these observations. Clinical and pathologic factors associated with a relative favorable prognosis of pancreatic metastasis are listed in Table 1 [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Eine Aufstellung von Hirota aus dem Jahre 1996 zeigt detailliert 66 Fa Èlle von Pankreasmetastasen eines Nierenzellkarzinoms [15]. [26]. Onishi gibt ein Duchschnittsalter von 48 Jahren an.…”
unclassified
“…Onishi gibt ein Duchschnittsalter von 48 Jahren an. Einen Geschlechtsunterschied oder einen Seitenunterschied der prima Èren Nephrektomie findet er nicht [26]. Das Stadium des Prima Èrtumors ist in der Regel niedrig, d. h. Stadium I oder II bei solita Èrer Pankreasmetastasierung [26].…”
unclassified
See 1 more Smart Citation